THE IMPORTED INPUTS AND FIRM EXPORT PERFORMANCE IN INDONESIAN TEXTILE AND APPAREL INDUSTRIES - Fransiskus Xaverius David Ardiyanto (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2020)
Limiting imported inputs for Indonesian textile and apparel industries may inadvertently decelerate the industries’ export performance, because each subsector in the industries has its own characteristics. This study analyzes the use of imported inputs and firms’ exports in the Indonesian textile and apparel industries. It has employed unbalanced panel data from 2000–2015 with year gaps and estimated them using regression model. The main findings show that foreign input has a positive and significant impact on the firms’ exports, and the effect is larger on the apparels than the textiles when the industries are detangled. Although the result suggests a positive connection, the government may not fully liberalize all imported inputs for the industries. Instead, they may implement an effective protection scheme by relaxing tariffs on imported inputs for domestic production and imposing high tariffs imported inputs that have the potential to compete with domestic finished products.